The Acoustic Effect of Windows Installed in a Wood Frame Façade - Jacek Nurzyński (Archives of Acoustics)
The acoustic effect of windows installed in a prefabricated wood frame façade was considered. Windows inserted into a lightweight wall modify its structural scheme. The research aimed to investigate the possible interaction of the façade’s main components and their actual contribution to the total sound insulation. The principal research question involved the prediction of the acoustic performance of the complete prefabricated panel from the performance of its basic elements, an opaque part and windows. As the frequency-dependent characteristics of the elements differ substantially, the use of single number values for prediction and accuracy was of particular interest. The study is based on laboratory measurements. Initially, two full-scale samples of an opaque wall and four windows were tested separately. Then, several variants of the façade consisting of various combinations of these elements were examined. The results of measurements were juxtaposed and compared with calculated values. The frequency-dependent experimental results were fairly consistent with calculations. The estimations based on single number quantities were also in good agreement with measurements. Thus, it may be concluded that the façade elements did not interact significantly, and the single number calculations give reliable results that can be used in practice.